Paint composition and delamination concerns in Ole Schwalbe's "Portrait of a Painting III", 1962 - Decq, Louise 1982-; Saverwyns, Steven; Kuvvetli, Filiz; Baadsgaard, Elizabeth (2024)
This study investigates the preservation challenges associated with Ole Schwalbe's Portrait of a Painting III (1962). The painting, an example of minimalist abstract constructivism, suffers from severe paint delamination. Analytical techniques such as SEM-EDX, THM-GC/MS, micro-Raman spectroscopy and FTIR have been used to examine the paint composition and identify the causes of instability. The results suggest that incomplete curing processes and oxidative degradation in the thickly applied black paint has caused zinc soap accumulation in the underlying zinc white preparation layer. The volume reduction of the upper layers, combined with a swelling of the lower, has contributed to the degradation observed. This research provides insights into the conservation of post-war abstract artworks.